The Book of Two Ways - Picoult, Jodi 1966- (New York : Ballantine Books, 2020)
"After my son Kyle Ferriera van Leer declared his major in Egyptology at Yale in 2010, he mentioned the Book of Two Ways in passing. Without knowing a thing about it, I said, "That's a great title for a novel." It was only after he began to explain what it actually was that I realized what I needed to write about - the construct of time, and love, and life, and death"--
Includes bibliographical references (pages 415-417).
Library Journal
Kirkus Reviews
Publishers Weekly
Booklist
Adult
Keywords: Archaeologists -- Fiction; Man-woman relationships -- Fiction; Families -- Fiction; Women -- Fiction